Critical Factor of The Disclosure of ISR in Manufacturing Company - Mega Arthika Dwi; Caesar Marga Putri; Etty Gurendrawati (RTTM, 2023)
The objective of this study is to test, demonstrate experimentally, and determine if the size of the board of commissioners, firm size, profitability, and liquidity have a link with ISR (ISR) disclosure to companies on the Sharia Securities list (DES). The manufacturing enterprises that were listed on DES and that had published successive annual reports between 2011 and 2017 made up the population for this research. In all, there were 273 samples taken for this research. This research makes use of the sampling approach known as purposive. Analysis techniques are carried out using multiple regression methods and classical assumption tests. The results of the study indicate that corporate size and profitability have a beneficial influence on ISR disclosure. Even though neither the size of the board of commissioners nor liquidity have any role in ISR disclosure.